The Politics of Contaminated Sites Management Institutional Regime Change and Actors’ Mode of Participation in the Environmental Management of the Bonfol Chemical Waste Landfill in Switzerland - Dupuis, Johann (Springer, 2015)
The Bonfol chemical waste landfill, one of the biggest of its kind in Switzerland, was in activity from 1961 to 1976. The formal procedure by the authorities demand ing the clean-up of the site started at the beginning of the year 2000, and the task will be accomplished approximately in 2016 with costs close to 0.5 billion CHF. As the clean-up is still going on, this book is the first published using this particular case of contamination. One may wonder why this interest in the Bonfol site rather than other cases of success or failure in contaminated sites remediation processes in Europe, and how the lessons from this book can be applied to environmental management...